Open Science in the Humanities, or: Open Humanities? - Marcel Knöchelmann (Publications, 2019)
Open science refers to both the practices and norms of more open and transparent communication and research in scientific disciplines and the discourse on these practices and norms. There is no such discourse dedicated to the humanities. Though the humanities appear to be less coherent as a cluster of scholarship than the sciences are, they do share unique characteristics which lead to distinct scholarly communication and research practices. A discourse on making these practices more open and transparent needs to take account of these characteristics. The prevalent scientific perspective in the discourse on more open practices does not do so, which confirms that the discourse’s name, open science, indeed excludes the humanities so that talking about open science in the humanities is incoherent. In this paper, I argue that there needs to be a dedicated discourse for more open research and communication practices in the humanities, one that integrates several elements currently fragmented into smaller, unconnected discourses (such as on open access, preprints, or peer review). I discuss three essential elements of open science—preprints, open peer review practices, and liberal open licences—in the realm of the humanities to demonstrate why a dedicated open humanities discourse is required.